Creep from the deep - "Stine, R.L" (Scholastic Inc.:, New York, 2008)
Billy and Sheena go with their Uncle, Dr. Deep, to search for treasure and are pursued by pirates who have been dead for two hundred years, and when Billy and Sheena return to land and visit Horrorland they encounter their worst fears
Keywords: Horror fiction